Antitumoral properties of butanolic fraction from leaves extract of Chrysobalanus icaco L. in breast and lung cancer cell lines. - Letícia Oliveira da Cruz; Bruna Barros Fróes; Luana Brito do Nascimento Araújo; Ísis Salviano; José Luiz Mazzei; Bianka Oliveira Soares; Rachel Fátima Gagliardi Araujo; Flávio José da Silva Dantas; Andre Luiz Mencalha (International Journal of Phytomedicine, 2020)
Infusion of leaves from Chrysobalanus icaco L., known as Icaco or Abajeru, is widely consumed in Brazil due to its therapeutic effects, such as hyperglycemia regulation, anti-inflammatory, analgesic and against chronic diarrhea. The aqueous and hydroalcoholic extract from Icaco also present anti-cancer properties, including colon cancer and leukemia. However, the antitumoral activity of the butanolic fraction still unknown. This study aimed to investigate the antitumoral properties of butanolic fraction against breast and lung cancer cell lines. Breast and lung cancer cell lines were incubated with the butanolic fraction (0.5, 1 and 5 µg.mL-1) for 24h. WST-1 and Trypan blue exclusion assays evaluated cell viability. The reactive oxygen species generation was measured, and the cell death pathway was analyzed by flow cytometry. The phytochemical profile was determined by thin-layer chromatography (TLC) analysis. The butanolic fraction presents triterpenes, flavonoids, and phenolic compounds as its major constituents. Cell proliferation of MDA-MB-231 and A549 were decreased by butanolic fraction (0.5, 1.0, and 5.0 µg.mL-1) treatment. Butanolic fraction (5.0 µg.mL-1) increase intracellular reactive oxygen species levels in MDA-MB-231, 118%, and in A549, 20%, cell lines. The loss of viability and reactive oxygen species increase was accompanied by apoptosis induction. The cellular migration of both cell lines was decreased by 13% in MDA-MB-231 and by 58% in A549 with the butanolic fraction of C. icaco. These results suggest that the butanolic fraction from Chrysobalanus icaco has anti-cancer properties against MDA-MB-231 and A549 cancer cells.